ANALISA RESISTIVITAS TANAH TERHADAP PREDIKSI KOROSI PADA PIPA DISTRIBUSI AIR BERSIH DI KAMPUS UNIMAL BUKIT INDAH - Reza Putra; Muhammad Muhammad; Abdul Rahman; Teuku Hafli; Nurul Islami (Malikussaleh University, 2022)
This study aims to predict corrosion in water distribution pipes at the Bukit Indah Unimal campus. Corrosion is the damage to chemical elements in a metal that changes the original properties of the metal. There are four kinds of processes for corrosion, namely, one anode loses electrons, two cathodes accept electrons, three liquids and four metals connect the cathode and anode. The geoelectric resistivity method is used to determine the soil resistance properties of the subsurface layer. The wenner 4 pin method is a geoelectric data retrieval that is often used with the same pin spacing arrangement. Res2Dinv is software that is on a computer to generate 2-dimensional images from the resistivity data obtained and determine the layer below the surface. From the inverse results, the smallest error value can be obtained when iterating up to 4 times, namely Java Road 45.3%, Sulawesi Road 49.6%, Kalimantan Road 30.6%, Sumatra II Road 46.1%, Main Gate 41.1% Sumatra I 23.4%. Based on the data, the measurable results below the surface range from 0.05 m to 5 m.